Minangkabau Language and Change in People’s Political Orientation - Gusti Asnan; Oktavianus Oktavianus (JURNAL ARBITRER, 2023)
This article discusses the change in the Minangkabau political orientation from the Dutch colonial era to the present. They pose the Minangkabau language as a political issue in the national interaction. This study employs content analysis and qualitative historical research methodologies. The content analysis approach is used to determine the accuracy of information gathered from many sources, as well as to describe and analyze the Minangkabau language’s politicization by the Minangkabau people, Dutch colonialism, and the government of The Republic of Indonesia. This paper shows how Minangkabau people view their mother tongue as a part of national identity, how they make it as the ammunition for the movement of resentencing to fight against the central government, how Minangkabau people make their mother tongue a part of ethnic identity politics; and how language policy of the Dutch colonial and Republic of Indonesia government influenced the change in Minangkabau political orientation. The analysis proves that language has become inseparable from regional history dynamism and Minangkabau regional-political life. The language attitude of the Minangkabau people in the colonial era showed a high national spirit. Language has the capacity to foster emotional connections among its proponents, whereas history can offer a comprehensive glimpse into the evolution and progression of language throughout time.